# Posts by Christiaan

Total # Posts: 84

Math
Just first plot the line where 3x+4y = 12 This is the line y = -(3/4)x + 3 Since you are dealing with the graph of an inequality, you will have to indicate an area where the inequality holds. since 3x+4y has to be less than or equal to -12, that area equals the area under the ...

Math
because the sign of the second degree term of the polynomial (x^2) is positive, its graph is a parabola with a minimum. So A is true. if you fill in -1 and 4 in the equation, you get 0, ergo the graph crosses the x-axis at -1 and 4. So F is true. For x = 0, y= -4, so the graph...

Physics for Life science
JUST NICE!!!

biology
stupid question

math
The first thing you should do is try to remove the brackets. You can do this by using distributivity. In symbols, this means the following: a*(b + c) = a*b + a*c As you can see, the first term of the equation is 7*(y+3) So, using distributivity, we find that 7*(y+3) = 7*y + 7*...

Math
This sequence is the Fibonacci sequence. Every number in this sequence is the sum of the two previous numbers: 1+1 = 2 1+2 = 3 2+3 = 5 3+5 = 8 5+8 = 13 The first seven numbers of the sequence are given, so to find the next four numbers add the two previous numbers. Then you ...

Science
You need to calculate the average force. For this, we use Newton's second law, which states that: F = m*a (where F stand for force, m is mass and a is acceleration). Since the mass of the person was already given, we only need to calculate the persons acceleration. One of ...

English!!!!!!!!!!!!
I would go with the first sentence. The word "female" isn't used that much in informal language and since the word "girl" already implies that the person is of the female sex, sentence nr. 3 has a word too many.

science
The answer would be "all of the above", because they are all plants or algae. Plants and algae are both autotroph organisms. This means they use the process of photosynthesis to produce glucose (type of sugar = food for the organism) from minerals using the sun's...

algebra 2
Using the substitution method means you first find one of the two variables (perhaps in terms of the other variable) and then 'substitute' this result in the other equation. If we apply it on this system we would work as follows: 1) Look at the second equation. You can...

Chemistry
Yes, that is correct.

Math
Yes

just to make sure. You have: (17-12)-(-15)/(-6)+3+6 ? Ok, the you do the following. The order of operations dictates that you 1) First work out the operations between brackets () 2) work out all the multiplications and divisions 3) work out all the additions and subtractions ...

Math
No it's not. You haven't considered the fact that the order in which he takes the audits doesn't matter. So e.g. the combination 1-2-5 would be the same as 5-1-2.

algebra 3
The polynomial would have to have 4 zeros, meaning it would have to be a polynomial of the 4th degree. The general form for a polynomial of the 4th degree with zeros a, b, c and d would be: f*(x-a)*(x-b)*(x-c)*(x-d) where f is a random real number (lets take this to be 1 in ...

math
Your answer is right. -x/2 + 4 = 12 so: -x/2 = 8 so: -x = 16 so x=-16 You can check this by filling in -16 in the equation: -(-16)/2 + 4 = 16/2 + 4 = 8 + 4 = 12

Math
Yes, that is correct. The sample space is the set of all possible outcomes of an experiment. Answer B gives the set off all those outcomes

The | | signs mean "absolute value". When you take the absolute value of a number, you always take the numbers positive value. So |-5| = 5, |-21| = 21, |24| = 24, |5| = 5, and so on. So, for the first expression, if we replace the x with 5, we get that: |2*x-15| = |(...

math
Well, when working with the less and greater signs (or inequalities as they are called), you can always work in the same as you would do with normal equation (in other words, just replace the less and greater signs with an equals sign). So for this equation you would get: -6+x...

from the first equation, x/y=4, we can find that x=4*y. If we fill this in into the second equation, we get that: x-y=9 <=> (4*y)-y = 9 <=> 3*y=9 <=> y=3 Knowing that y=3, we fill this in into our first equation and we get that: x=4*y, so that x=4*3=12 So, y=...

Calculus
The diameter of the sphere is decreasing at 0.2 cm/min. This means that its radius is decreasing by 0.1 cm/min. We also know its current radius is 8 cm. The formula for the volume of a sphere is: V= (4/3)*Pi*r^3 So, we can calculate the volume difference in 1 minute, by ...

Calculus
The diameter of the sphere is decreasing at 0.2 cm/min. This means that its radius is decreasing by 0.1 cm/min. The formul

algebra
well, first divide 1 billion by 3600*24*365=31536000. This is the number of seconds in one year. You will find that 1000000000/31536000=31.7097 So, now you know there are 31 whole years in that 1 billion seconds. Next you subtract that 31 years from your original 1 billion ...

math
(m^5)*m = m^5*m^1 = m^(5+1) = m^6 (m^6)^-7 = m^(6*-7)=m^(-42) m^(-42)/(m^(-32)*n^8) = m^(-42-(-32))*n^(-8) = m^(-10)*n^(-8) (=ANSWER)

cranberries

math 115 #17
I don't understand the reasoning behind your answer. Anyway, the way to do this is the folliwing. For every year your money is on the bank, the bank multiplies your balance by 1.05. This means that after 3 years, you get the following: Money after 3 years = inititial ...

physics
This is impossible to answer this way, since the initial amplitude isn't given.

physics
f = sqrt(k/m) where f is the frequency, k is the spring constant of the four springs, and m is the mass of the car. => k = f²*m = (3 Hz)²*1400 kg =12600 N/m This results is the results for the total of the four springs, so for one spring we divide the answer by ...

physics
Sorry, made an error in my reasoning. Amplitude is correct, but speed and acceleration isn't. For a body undergoing simple harmonic motion, the expression for the maximum speed is: v(max) = A*f = 0.001 m * 118 Hz = 0.118 m/s and the expression for the maximum acceleration ...

physics
a) A= 2.0 mm /2 = 1.0 mm = 0.001 m b) The time it takes the blade to go back AND forth (the period of the oscillation) can be found as follows: T=1/f= 1/118Hz = 0.00847 s So, for the blade to cross the distance of 0.002 m, it takes 0.00847/2 s = 0.00424 s. v = x/t = 0.002 m / ...

physics
g = (G*M)/r² Where G is The gravitational constant, M is the mass of earth, and r is the distance from the center of the earth. Given this formula, you should be able to calculate the distance (for data about earth's mass and radius, search wikipedia for "Earth&...

physics
b) Since F = m*a The average stopping force can be calculated as: F = 72 kg* -294.25 m/s² = -21.186 kN The negative sign for both the acceleration and stopping force means they are poiting upward, since we took the downward direction to be positive.

physics
a) First you calculate his speed of impact (the speed when he hits the ground). For this you can use the formula: v² = v0² + 2.a.x where: -v is your final speed -v0 is your initial speed (0 m/s in this case) -a is your acceleration (the gravitational acceleration in ...

physics
b) According to Newton's 3rd law, for every action there is an equal but opposite reaction. This means that if the pole exerts a force of 493.12 N on the firefighter in the upward direction, the firefighter must also be exerting a force on the pole of 493.12 N in the ...

physics
a) Normally, al objects on earth fall with the same (nearly constant)acceleration (namely 9.81 m/s²). We see here that the firefighter only slides down the pole with an acceleration of 3.11 m/s². This means, that in order to slow down the firefighter, there must be ...

Physics
Kind of a strange question, since every object can have a varying velocity while having a varying speed. When you talk about speed, you are referring to a quantity (e.g. John travels with a SPEED of 2 mph). When you talk about velocity, you also talk about a quantity, but you ...

Biology
In the final step of DNA extraction from E. Coli bacteria, we used ethanol so that the DNA would precipitate. Why is it that DNA precipitates in ethanol, and not in water? Both of them are polar solvents, and so is DNA. So why doesn't water make DNA precipitate?

Biology

Biology
For one of our lab sessions, we had to isolate DNA from E. Coli bacteria. During one of the steps in the isolation process, we had to use SDS(Sodium lauryl sulfate) at 60°C. One of the questions was: Why do we use SDS, and why at this temperature. I already found out that ...

food
It is true that the tomato is frequently used in italian cooking. So if that's what you meant to say, then you're right. However, the tomato was originally cultivated in South America, after which it was brought to Europe.

Math
If you look carefully at the two terms of the sum, you can see that in each term there is a sqrt5. So, you can write the sum as: sqrt(5)*(9-3) = 6*sqrt(5)

Math
You have to remember that i² = -1. so, when you apply the distributive property: (-8+i)/(2-3i) = -8*2 + 8*3*i + 2*i - 3i² = -16 + 26*i +3

Math check
Yes, that is correct

Math

Math
You forgot to multiply sqrt(x) with -3sqrt(x) and add this to the result. If you do so, you get an additional term with -3x

Math check
^5 sqrt symbol a^6 = a^(6/5) and ^4 sqrt symbol a^3 = a^(3/4) a^(6/5)*a^(3/4) = a^((6/5)+(3/4)) = a^(39/20) = ^20sqrt symbol a^39

Math check
I've did the calculations, and I get 20sqrt symbol a^39

Math
kilograms

Math
for ther first square root we can do the following: Since y² has an even exponent, we can divide the exponent by 2 and put the y outside of the root. x^5 can also by written as x*x^4. Since x^4 has an even exponent, we can divide the exponent by 2 and put x^2 outside of ...

math
C)radius circumference = 2*Pi*radius Diameter = 2*radius Since Pi is approximately 3,14, the circumference is approximately 6,28 times bigger than the radius. The diameter is 2 times as big as the radius

math
Given is that the ratio of height is 1:100. This means that for every unit of height in the photograph, the real object is 100 times as large. So, e.g. if we have an object that measures 20 cm on the photograph, this means the object is 2000 cm in real life. So if you have a ...

Maths
I don't really know how much you know about mathematics, but I'll give you some basic steps in sketching a function. 1) find the domain of the function. You can't draw the curves in places where the function can't go. (For polynomials of x, the function reaches...

French
1st sentence "de les gens jeunes" has to be "des gens jeunes" and "à les jeunes" has to be "aux jeunes" since there is a contraction between "de" and "les" and between "à" and "les". ...

chemistry`
Hybrid cars are cars that run on both petroleum (i.e. gas) and another type of energy source (e.g. electricity from batteries, hydrogen, etc.). What you have to do for this question is find a use for petroleum in hybrids outside serving as a fuel. You could look up "...

geometry
Yes they do. An altitude is a line that contains one corner of the triangle and is perpendicular to the side across this corner

geometry
The easiest way to do this is find 2 of the 3 altitudes of the triangle and look where they intersect. This point is the orthocenter.

Math
Taking a certain percentage of a number means dividing this number by 100 and then multiplying this number with the given percentage. So we get that: 3,17392% of 3,123= (3,123/100)*3,17392= 0,0991215216

science
3)D 4)D 25)A When we look in the periodic table of elements, we find that copper has an atomic weight of 63,5 g/mol => 34g/(63,5g/mol) = 0,54 mol 26)A Using the previous exercise as an example, we are able to calculate the number of mol in 22 grams of copper => 22g/(63....

math
This one is easy. x is already expressed in terms of y in the second equation. You only have to replace the x in the forst equation with the expression from the second equation. You get that: 3*(y+2)-4y=-5 =>3y+6-4y=-5 =>6-y=-5 =>y=11 When we place this value for y in...

Bio lab question 2
I think that really depends on the kind of reaction. An enzyme is a biological katalyst for a reaction, meaning it will speed up, or slow down, a reaction, depending on the desired effect. Adding an acid to a reaction can have all kinds of effect. Can you give us any more ...

Science
Yes, it does. Acceleration is expressed using a vector. This means that it doesn't only have a magnitude, it also has a certain direction (as does the velocity). When a body is in orbit, the MAGNITUDE of it's velocity stays constant, but the DIRECTION of the velocity ...

math
When we look at the second equation, we can transfer the term 2x to the other side of the equality. We get that: 2x+y = -1 <=> y = -1-2x when we replace the y in the first equation by the value we just calculated, we get that: 4x + 3y= -3 <=> 4x + 3(-1-2x)=-3 <...

Bio
The purpose of your experiment is to show that certain reactions are speeded up by using a catalyst (in this case H2O2). These catalysts only work when they act on certain materials. That's why you are using sand to show that the hydrogen peroxide doesn't just react ...

algebra
We have 2 fractions here. The first thing you want to do is equal the entire expression to 0 (in order to solve for x). So we get that: ((x+4)/(x^2-x-6))+ ((3x-2)/(x^2+3x+2))=0 Now, we can transfer one of the fractions to the other side of the equation. We get that: ((x+4)/(x^...

algebra
I don't think your answer is correct. We can write 600 as 6*100 So, we can also write the sqaure root of 600 as: sqrt(600)=sqrt(6*100) = sqrt(6)*sqrt(100) The square root of 100 is 10, so we get that: sqrt(600)=10*sqrt(6) This is the simplest way to write the square root ...

math
Lets assume you want to solve for either x or y. 1) If you want to solve for x, we have to take y=0. When we fill this into the equation, we get that: -4X+0=16 => -4X=16 => X=-4 2) If you want to solve for Y, you have to take x=0. When we fill this into the equation we ...

Algebra
No, your answer is wrong. When you multiply a number with a power of 10, you just have to move the decimal point the same number of places to the right as the exponent of the power of ten indicates. So e.g. if we have 10^6*5.6, we move the decimal point 6 places to the right, ...

Algebra
No, when we take the sqrt of a squared term, we get that term, or its negative. So, sqrt(x²)=x or sqrt(x²)=-x So for this question we get that: sqrt((a+8)²)=a+8 or sqrt((a+8)²)=-a-8

Trigonometry
2) csc(x)=1/sin(x) and cot(x)=cos(x)/sin(x) => cot^3(x)/csc(x)=cos^3(x)*sin(x)/sin^3(x) =cos^3(x)/sin²(x) Now, we know that cos²(x)=1-sin²(x) => cos^3(x)=cos(x)*(1-sin²(x))=cos(x)-cos(x)*sin²(x) So, when we fill this in in the equation we get ...

Trigonometry
1) csc²(x)=1/sin²(x) and cot(x)=cos(x)/sin(x) => csc²(x)/cot(x) = sin(x)/(sin²(x)*cos(x)) We can scrap one of the sinus factors in both the numerator and denominator, so that the expression equals: 1/(sin(x)*cos(x)) Since csc(x)=1/sin(x) and sec(x)=1/cos...

chemistry
There is a constant in chemistry, know as Avogrado's number, which equals 6.023*10^23. This number equals the number of particles of a random material in exactly one mol of material. The mol is thus defined as containing exactly that number of particles. Now, since it'...

math
Well, the general approach to solving equations of this kind is by using something known as a determinant. The determinant of this equation is found by the following formula: D=b²-4ac (this formula is found by using Horners theorems on second degree equations, but I won&#...

Math
First of all you may want to simplify the left side of the inequality. We get: 6x-10>2x+6 Now, I don't now if you have any experience in solving regular equations, but inequalities work in exactly the same way. The only exception to this is that when you transfer a ...

Math
If we take the speed of the freight train to be x, and the speed of the passenger train to be y, we get that: 1)y=x+12 2)270/y=210/x So if we replace y in the second equation by the y we found in the forst equation, we get that: 270/(x+12)=210/x =>210*(x+12)=270x =>60x=...

AP physics
Torque is calculated by the formula: t=r.F.sin(a) where a is the angle between the rod and the force acting on the rod(=25°), r is the distance from the force to the pivot point(which is 1m), and F is the gravity force acting on the ball(=m.g = 0.85kg.10m/s² =8.5 N) ...

physics
First we calculate the torque. t=rxF=r.F.sin(b) where is the angle between r and F (which in this case equals 90°). So in this case t= r.F = 0,15m.F = 0.075t + 0.045t² We also know that I = 1.5 . 10^-3 kg.m² and so we can calculate the angular acceleration (a) ...

math
The slope of the line is 1, so a=1. Since the slope of a line equals the tangent of the angle between the x-axis and the line, we find that: tan(angle) = 1 So if we take the arctangent (which is the inverse of the tangent function) of 1, we find that the angle must equal 45°.

algebra
I don't see how this expression could be simplified any further since it is already in its most basic form. The only thing you could do is switch the two terms between the brackets so you get (2x-5)².

math
@drwls: The solution you provided is correct, however, it was asked that this system be solved by means of substitution. In the second equation, it is given that y=-3x-12. Simply by replacing (i.e. substituting) y in the first equation by the value that was given for y in the ...

science
I found some info on wikipedia about this subject(just google for volcano+wikipedia) Basically, the explosive power of a volcano depends on the composition of its magma. If the magma contains high amounts of silica (>63%), gases are trapped within, and cause enormous ...

Chemistry
The answer I gave you is in fact correct. I just had a course in numerical mathematics, and because you are working with very small numbers (in the order of 10^-5), there can be relatively large errors when you plug in the solution for x in the equation. Note however that the ...

Chemistry
I went ahead and did the calculations for you. I find that x is 0.001331654593 or x is -0.001331654593. I read your previous post and since you are looking for a concentration of ions, only the positive value matters. So you have 0,133 x 10^-2 mol/l H+ ions. If you want to ...

Chemistry
At first, you should transfer the denominator of the fraction on the right side of the equation to the left side of the equation. Then you get: (0.10-x) x 1.75 x 10^-5 = x^2 => (1,75 x 10^-6)-(1.75 x 10^-5 x) = x^2 => x^2-(1.75x10^-5 x)-1.75 x 10^-6 = 0 This is a ...

1. Pages:
2. 1

Post a New Question